Turning Knowledge into Impact : How English Education Alumni Excel in Education? (An Application of Qualitative Personal Narratives Method) - Irwan, Dedi; Pratama, Bima; Felice, Imel Oktaviani; Batuah, Jelisca Chellsy Timol (IKIP PGRI Pontianak, 2024)
This research explores the inspiring stories of English education program alumni who have pursued careers in education. It aims to identify the factors that motivated these individuals to choose a career in education and the impact of their English education on their professional development. This study uses a qualitative research design, which involves in-depth interviews with one of the alumni of University in Pontianak English education program who is currently working in the education sector. Through their personal narratives, the research will explore their career journeys, challenges faced, and key factors that contributed to their success. The research aims to provide inspiration for students and educators, as well as providing valuable insights for the curriculum development of English education programs. The research findings show that participants were influenced by their passion for teaching and the desire to do good in students' lives. They also emphasized the importance of their English education in developing communication, critical thinking and problem-solving skills. The study concluded that the inspiring stories of English education program alumni who made a career in education can serve as a valuable resource for current students and future educators. The research findings suggest that English education can play an important role in shaping career choices and professional development, especially in the field of education.